Sniffing and Spoofing in Computer Security - Saddam RA; Angga Pranata; Sugiono; Rizki Zulanggara; Nur Halimah; Sri Nur H; Rosdiana SM; Nurhalim; Aprina Handayani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The development of Information Technology (IT) has changed people's mindset. The presence of the Internet as the main platform for online activity is vulnerable to criminal acts by irresponsible parties. Criminal acts in cyberspace, of course, pose a major threat to the governance of online activities. One of these major threats is the threat of network security. Networks connected to the internet are basically insecure and can always be exploited by hackers, both LAN and wireless networks. The internet network has two data transmission media, namely wired and wireless. what happens is open. Examples of network security threats that often occur are sniffing of activities on the network (sniffing) and also impersonation by other people (spoofing). This resume article aims to identify criminal acts that threaten computer security, namely Sniffing and Spoofing